META analysis on the effect of taijiquan on improving negative psychological symptoms of college students and the optimal dose - Du, Zhihao; Zhang, Xiuli; Qin, Hao; Wang, Ruiqi; Bai, Yunxia; Yao, Xiaonan (Frontiers in Public Health, 2022)
Background Taijiquan, as a physical and mental exercise, can improve the negative psychology of college students. However, it is still controversial, and the optimal exercise dose of taijiquan to interfere with negative psychology has not been evaluated. Objective This study is aimed at systematically evaluating the effect of taijiquan therapy on improving negative psychological symptoms of college students and its optimal intervention dose. Methods Search databases such as Web of Science, Embase, PubMed, CNKI, WFSD, etc. Collect high-quality relevant RCT studies. After screening, extracting, coding and counting the data, a META analysis is done through Review Manage 5.3 and Stata 15.0 software. PICOS established the eligibility criteria to select the studies as follows: (i) population - non-clinical of college students; (ii) intervention - taijiquan intervention; (iii) comparison - taijiquan intervention group and regular physical activity group; (iv) outcomes - depression, anxiety; and (v) study design - randomized controlled trial. Results A total of 12 articles and 1,000 samples were included. All of the participants are college students. Taijiquan therapy can significantly reduce the depression and anxiety symptoms of college students [SMD = −0.53, 95% CI (−0.82, −0.23)], [SMD = −0.49, 95% CI (−0.90, −0.09)], with statistical significance (P < 0.05). Subgroup analysis shows that: there is a precise focus on depression and anxiety symptoms. The intervention period is more than 12 weeks, and the best effect appears when people practice 3 times a week. The best single intervention time for depression symptoms is 60 min, and for anxiety symptoms 80–90 min. It is found that taijiquan combined with mindfulness intervention can significantly reduce negative psychological symptoms like depression and anxiety of college students than single taijiquan intervention. Funnel plot combined with sensitivity analysis, Begg, Egger test showed no publication bias. Conclusion Taijiquan intervention can effectively improve the negative psychological symptoms of college students, and it has great promotion value in colleges and universities. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022314071.